Two new species of Oxynoemacheilus from the Tigris drainage in Iraqi Kurdistan (Teleostei: Nemacheilidae) - Freyhof, Jörg; Abdullah, Younis Sabir (Zootaxa, 2017)
Two new species of Oxynoemacheilus are described from the Sirvan River drainage in Iraqi Kurdistan. Oxynoemacheilus gyndes, new species, is distinguished by having a very short lateral line, reaching behind the pectoral-fin base, no scales except on the posteriormost part of the caudal peduncle, a slightly emarginate caudal fin and no suborbital groove in males. Oxynoemacheilus hanae, new species, is distinguished by having a midlateral row of elongated blotches, isolated patches of dark-brown spots or blotches on lower flank, a deeply emarginate caudal fin and a suborbital groove in males.